Prognostic Value of Stress Hyperglycemia Ratio for In-Hospital Mortality in Diabetic Patients After ST-Segment Elevation Myocardial Infarction - Muhammad Junaid; Bhatti, Khalid Iqbal; Muhammad Shakil; Jamil Ur Rahman; Shahid Zaman; Muhammad Idrees (Indus Journal of Bioscience Research, 2025)
Background: Stress hyperglycemia is a common occurrence in patients with ST-segment elevation myocardial infarction (STEMI), but in diabetic individuals, distinguishing acute hyperglycemic stress from chronic glycemic status poses a clinical challenge. Objective: This study aimed to evaluate the prognostic value of SHR for predicting in-hospital mortality in diabetic patients after STEMI. Methods: This descriptive study was conducted at the Department of Cardiology, National Institute of Cardiovascular Diseases, Karachi, from 26 February 2025 to 26 May 2025. A total of 192 diabetic patients presenting with STEMI were enrolled using non-probability consecutive sampling. SHR was calculated as the ratio of admission blood glucose to estimated average glucose derived from HbA1c. Patients were categorized into high SHR (>1.19) and low SHR (≤1.19) groups. Results: The mean age of patients was 58.6 ± 10.4 years, with 68.8% males. High SHR was observed in 53.1% of patients. The overall in-hospital mortality rate was 14.6%. In-hospital mortality was significantly higher in the high SHR group (21.6%) compared to the low SHR group (6.7%) (p = 0.008). Stratification showed that high SHR remained significantly associated with mortality across various subgroups, independent of age, gender, BMI, duration of diabetes, and treatment type. Conclusion: It is concluded that a high stress hyperglycemia ratio is an independent and significant predictor of in-hospital mortality among diabetic patients presenting with STEMI. Incorporating SHR into initial clinical assessment may improve risk stratification and guide early management strategies in this high-risk population.